miRNA-dependent target regulation: functional characterization of single-nucleotide polymorphisms identified in genome-wide association studies of Alzheimer’s disease - Delay, Charlotte (Alzheimers Res Ther, 2016)
BACKGROUND: A growing body of evidence suggests that microRNAs (miRNAs) are involved in Alzheimer’s disease (AD) and that some disease-associated genetic variants are located within miRNA binding sites. In the present study, we sought to characterize functional polymorphisms in miRNA target sites within the loci defined in earlier genome-wide association studies (GWAS). The main objectives of this study were to (1) facilitate the identification of the gene or genes responsible for the GWAS signal within a locus of interest and (2) determine how functional polymorphisms might be involved in the AD process (e.g., by affecting miRNA-mediated variations in gene expression). METHODS: Stringent in silico analyses were developed to select potential polymorphisms susceptible to impairment of miRNA-mediated repression, and subsequent functional assays were performed in HeLa and HEK293 cells. RESULTS: Two polymorphisms were identified and further analyzed in vitro. The AD-associated rs7143400-T allele (located in 3′ untranslated region [3′-UTR] of FERMT2) cotransfected with miR-4504 resulted in lower protein levels relative to the rs7143400-G allele cotransfected with the same miRNA. The AD-associated rs9909-C allele in the 3′-UTR of NUP160 abolished the miR-1185-1-3p-regulated expression observed for the rs9909-G allele. CONCLUSIONS: When considered in conjunction with the findings of previous association studies, our results suggest that decreased expression of FERMT2 might be a risk factor in the etiopathology of AD, whereas increased expression of NUP160 might protect against the disease. Our data therefore provide new insights into AD by highlighting two new proteins putatively involved in the disease process. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13195-016-0186-x) contains supplementary material, which is available to authorized users.